Business Strategy Formulation for Kampung Wisata Sentul - Widyaningrum, Nessi Ovannia; Ghazali, Achmad (The Indonesian Journal of Business Administration, 2015)
Abstract - Kampung Wisata Sentul is one of the UID projects to support community development and spread environmental education to visitors through educational platform formed as agritourism. Since its opening to public in 2014, KWS has faced four business issues that consist of infrastructure and facilities resulting in visitorsâ€™ cancellation, the burden of its operational cost, lack of marketing resulting to lack of brand awareness, and no evaluation system to measure the impact of KWS to local community and visitors. This research is focused to get into the proper solutions for KWS to reach its sustainability. The business strategy formulations for KWS are proposed empowerment programs for local community, deepened experimental and experiential learning for the visitors, recommended marketing activities, and evaluation system with BSC along with strategic initiatives and KPIs. These solutions are also supported the triple bottom line approach and implementation plan with the purpose that KWS can reach its sustainability.Â Keywords: Community Development, Agritourism, Social Profit, The Triple Bottom Line, Strategy Formulation